Modular and Versatile Trans‐Encoded Genetic Switches. (27th July 2020) - Paul, Avishek; Warszawik, Eliza M.; Loznik, Mark; Boersma, Arnold J.; Herrmann, Andreas
Abstract: Current bacterial RNA switches suffer from lack of versatile inputs and are difficult to engineer. We present versatile and modular RNA switches that are trans‐encoded and based on tRNA‐mimicking structures (TMSs). These switches provide a high degree of freedom for reengineering and can thus be designed to accept a wide range of inputs, including RNA, small molecules, and proteins. This powerful approach enables control of the translation of protein expression from plasmid and genome DNA. Abstract : Switch‐hitter : A bacterial genetic switch that accepts RNAs, small molecules, and proteins as inputs was developed based on a tRNA‐mimicking structure. The switch is trans‐encoded, which makes manipulation of the target mRNA redundant. It is stable to RNase, shows a strong dynamic response, and exhibits a high level of orthogonality.